Data from: Time for recovery of riparian plants in restored northern Swedish streams: a chronosequence study - Hasselquist, Eliza Maher; Nilsson, Christer; Hjältén, Joakim; Jørgensen, Dolly; Lind, Lovisa; Polvi, Lina E. (2015)
A lack of ecological responses in stream restoration projects has been prevalent throughout recent literature with many studies reporting insufficient time for recovery. We assessed the relative importance of time, site variables, and landscape setting for understanding how plant species richness and understory productivity recover over time in riparian zones of northern Swedish streams. We used a space-for-time substitution consisting of 13 stream reaches restored 5–25 years ago, as well as five unrestored channelized reference reaches. We inventoried the riparian zone for all vascular plant species along 60-m study reaches and quantified cover and biomass in plots. We found that while species richness increased with time, understory biomass decreased. Forbs made up the majority of the species added, while the biomass of graminoids decreased the most over time, suggesting that the reduced dominance of graminoids favored less productive forbs. Species richness and density patterns could be attributed to dispersal limitation, with anemochorous species being more associated with time after restoration than hydrochorous, zoochorous, or vegetatively reproducing species. Using multiple linear regression, we found that time along with riparian slope and riparian buffer width (e.g., distance to logging activities) explained the most variability in species richness, but that variability in total understory biomass was explained primarily by time. The plant community composition of restored reaches differed from that of channelized references, but the difference did not increase over time. Rather, different time categories had different successional trajectories that seemed to converge on a unique climax community for that time period. Given our results, timelines for achieving species richness objectives should be extended to 25 years or longer if recovery is defined as a saturation of the accumulation of species over time. Other recommendations include making riparian slopes as gentle as possible given the landscape ...